Advancing the Diagnostic Value of the Pro-Agility Shuttle and the Acute and Chronic Effects of Training with Wearable Resistance on Pro-Agility Shuttle Performance - Forster, James (Auckland University of Technology, 2023)
The ability to change directions effectively is critical in many sporting scenarios. Thus there is importance for practitioners to assess and develop change of direction (COD) ability in athletes, with tests such as the 5-0-5 and pro-agility shuttle tests. While, empirical efforts had been made to improve the analytical quality of COD assessments by delineating between the linear sprint and COD components, there had been no evidence of researchers differentiating between the different components for the pro-agility shuttle. Adopting such an approach could provide better diagnostics and exercise prescription. Wearable resistance (WR) in the form of limb micro-loading has led to enhanced performance of sport-specific movements, without compromises to velocity or movement specificity during training. Yet, there was no evidence in the research to date of the acute and chronic effects of WR training on COD performance, specifically in the pro-agility shuttle. The focus of this thesis was to advance the diagnostic capabilities of the pro-agility shuttle and understand the training implications of shank and forearm WR training on pro-agility shuttle performance. The introductory chapter provided an overview of COD assessment, trainability of COD, and WR utility in a sport-specific context. This determined the framework of the thesis and necessity for exploration into diagnostic capabilities and WR utility as a novel training method. Two systematic reviews relating to the pro-agility shuttle were conducted. Firstly, Chapter 2 found timing light and stopwatch technologies to be most commonly used to assess the pro-agility shuttle, with total-time being the most reported value and therefore of limited value to the practitioners. Additionally, normative values were established with elite athletes being the fastest (4.61 ± 0.29 s) while sub-elite and novice athletes had similar spreads in performance (4.33 to 4.86 s). In Chapter 3, non-specific and specific training methods were reviewed the main findings being that sprint training (0.11 effect size (ES)), plyometric training (0.09 ES), resistance training (0.09 ES), and a combination of these training methods (0.08 ES) were found to be most effective at enhancing pro-agility shuttle performance. Furthermore, it was apparent that changes in pro-agility shuttle performance in response to WR training had yet to be investigated. These reviews highlighted important gaps and limitations and therefore provided a more focused direction for the experimental chapters of the thesis. To gain understanding of how the pro-agility shuttle could be used to differentiate between linear and COD components, the test was segmented into acceleration, deceleration, COD and reacceleration phases. Two experimental repeated measures studies were used to determine the reliability of this advanced diagnostic pro-agility protocol using timing light and radar technology. In Chapter 4, low typical error (coefficient of variation (CV) = 0.95 to 4.42%) and excellent relative consistency (intraclass correlation coefficient (ICC) 0.90 to 0.99) between sessions 2-3 for phases of the pro-agility shuttle was observed. In Chapter 5, the reliability of radar velocity profiling was investigated and was found to have acceptable absolute consistency (CV = 3.16 to 7.07%), yet relative consistency ranged from “very poor” to “good” (ICC = 0.14 to 0.76) between sessions 2-3. In Chapters 6 and 7 the acute and chronic implications of shank and forearm WR on pro-agility shuttle performance were investigated. Chapter 6 used a randomized cross-over design to compare the acute effects of 1.5% body mass (BM) shank (WRs) and forearm (WRf) WR loading on the pro-agility shuttle in twenty-eight team sport athletes. Compared to unloaded, WRs loading had significantly faster COD1 time (-12.8%, d=-0.49, p<0.05) and total-time (-10.6%, d=-0.90, p<0.05), while WRf had significantly slower linear speed time during the acceleration (ACC) 2 phase (6.98%, d=0.47, p<0.05). In Chapter 7 the effects of six-week progressively overloaded WRs and WRf COD training compared to unloaded COD training in forty-two team sport athletes were compared. Chronic WR training over a 6-week period did not result in any significant change to pro-agility shuttle total-time. Significant slower reaccelerative performance (24.11%, d = 0.84, p = 0.01), and faster sprint times (d = -0.55 to -0.60) were found following WRs compared to unloaded training. Significantly faster ACC1 time (-8.60%, d = 1.39, p = 0.04), yet slower in ACC2 time (41.54%, d = 0.94, p = 0.00), and shorter horizontal jump distance (d = -1.12 to 0.09, p <0.01) were observed after WRf compared to unloaded training. Chapter 8 provided an overall summary of the findings, detailed practical applications, and proposed future research directions. It is suggested for practitioners to use the advanced diagnostic protocol to better assess athlete performance in the pro-agility shuttle. Furthermore, WR COD training can be used to overload sport-specific actions and is beneficial to the development of COD associated athletic qualities.